Multi‐Component Approach for Synthesis of Quinolinyl‐1, 4‐dihydropyridines, Evaluation of Cytotoxicity against MCF7 and Molecular Docking Studies. Issue 34 (8th September 2020) - Suresh, Selvendran; Das, Souvik; Waidha, Kamaran; Maity, Ritwik; Basu, Biswarup; Rajendran, Saravanakumar
Abstract: Tetrazolo[1, 5‐ a ]quinoline‐4‐carbaldehyde, 3‐oxo‐3‐phenylpropanenitrile, and β‐enamine were reacted in one‐pot to obtain highly functionalized quinolinyl‐1, 4‐dihydropyridines. In addition to spectroscopic characterization, the structure of one of the compound is confirmed by single‐crystal X‐ray diffraction. Among all compounds evaluated for cytotoxic effect against MCF7, three quinolinyl‐1, 4‐dihydropyridines (SKS13, 19, and 20) were found to be most active with half inhibition concentrations value of 7.87–9.55 μM. Molecular docking of the active molecules to various breast cancer targets revealed effective compounds have multiple receptor targeting potential in breast cancer. Our results corroborate quinolinyl‐1, 4‐dihydropyridines as a valuable scaffold to develop anticancer drugs. Abstract : Eleven new highly functionalized quinolinyl‐, 4‐dihydropyridines synthesized via a one‐pot multicomponent process. The compounds, SKS13, 19, and 20 exhibited high cytotoxicity against MCF7 with IC50 values of 9.11, 7.87, and 9.55 μM respectively. Molecular docking conducted to elucidate inhibitory action.